Cost–Utility of Bilateral Versus Unilateral Cochlear Implantation in Adults: A Randomized Controlled Trial. Issue 1 (January 2016) - Smulders, Yvette E.; van Zon, Alice; Stegeman, Inge; van Zanten, Gijsbert A.; Rinia, Albert B.; Stokroos, Robert J.; Free, Rolien H.; Maat, Bert; Frijns, Johan H. M.; Mylanus, Emmanuel A. M.; Huinck, Wendy J.; Topsakal, Vedat; et al.
Abstract : Objective: To study the cost–utility of simultaneous bilateral cochlear implantation (CI) versus unilateral CI. Study Design: Randomized controlled trial (RCT). Setting: Five tertiary referral centers. Patients: Thirty-eight postlingually deafened adults eligible for cochlear implantation. Interventions: A cost–utility analysis was performed from a health insurance perspective. Main Outcome Measures: Utility was assessed using the HUI3, TTO, VAS on hearing, VAS on general health and EQ-5D. We modeled the incremental cost per quality-adjusted life year (QALY) of unilateral versus bilateral CI over periods of 2, 5, 10, 25 years, and actual life-expectancy. Results: Direct costs for unilateral and bilateral CI were [Euro sign]43, 883 ± [Euro sign]11, 513(SD) and [Euro sign]87, 765 ± [Euro sign]23, 027(SD) respectively. Annual costs from the second year onward were [Euro sign]3, 435 ± [Euro sign]1, 085(SD) and [Euro sign]6, 871 ± [Euro sign]2, 169(SD), respectively. A cost–utility analysis revealed that a second implant became cost-effective after a 5- to 10-year period, based on the HUI3, TTO, and VAS on hearing. Conclusion: This is the first study that describes a cost–utility analysis to compare unilateral with simultaneous bilateral CI in postlingually deafened adults, using a multicenter RCT. Compared with accepted societal willingness-to-pay thresholds, simultaneous bilateral CI is a cost-effective treatment for patients with a life expectancy of 5–10 years or longer.